Fenomena Kastrasi Linguistik Pada Teks Hasil Terjemahan Skripsi Mahasiswa Pendidikan Bahasa Arab Tahun 2015 - Akla, Akla (JURNAL TARBAWIYAH, 2015)
Linguistics castration is a phenomenon in which the linguistic elements of BSU text can not be automatically translated without omitting its intact meaning. From the description of the data, it can be concluded that the results of Indonesian translation into Arabic on studentsâ Undergraduate Thesis from Arabic Education Study Program (PBA) State is lamic College (STAIN) Metro 2014 found that there were many castration of linguistics. An interesting finding was that the result of studentsâ translation was caused by most of them were mainly focus on word for word meaning rather than the context of meaning itself. One the reasons is their inability to translate words to find the special meaning content and detect the relevance of a word with other words in wider text. In addition, more students tend to translate all the words in text of BSU (in this case is Indonesian) though the text contains words that indicate the castration of linguistics, such as empty words (expletive), non-restrictive adjectives, appositive and restrictive or non-restrictive meaning. Having more knowlegde about linguistic castration will help the students to increase their understanding in translation process. Thus, they will get much better result of translation, as what is done by an expert Â of translator.